JARINGAN ULAMA KENDAL ABAD KE 19-20 - Ismawati, Ismawati (Badan Litbang dan Diklat Kementerian Agama RI, 2005)
This research shows intellectual relationship of four ulama of Kendal, i.e. Ahmad Rifa'i, Muhammad Idris, Muhammad Hadi and Ahmad Abd al-Hamid with ulama of Mecca in the 19th and 20th centuries. They familiarize Islam and gradually reform religious teachings to improve religious character in Kendal. In term of dissemination of ideas Ahmad Rifa'i, Muhammad hadi and Ahmad use the same media: i.e. writings. Meanwhile, Muhammad Idris is well-known as teacher for some prominent ulama and he himself memorizes the Qur'an. The reform focus on the reconstruction of socio-morality and emphasize on obedience to shari'a over tasawwuf.